THE INFLUENCE OF THE COMPLETENESS OF BPJS CLAIMS ON THE QUALITY OF CLAIMS AT MUHAMMADIYAH HOSPITAL BANDUNG - Sophia Sastri, Melin; Gunawan, Erix (Universitas Efarina, 2024)
This study aims to determine the effect of the completeness of BPJS outpatient claim requirements on the quality of claims at the Muhammadiyah Hospital in Bandung. The research method used by the author is quantitative with a descriptive approach. The data collection techniques used were observation, literature study, and questionnaires. The sampling technique used a simple random sampling technique with a sample of 100 outpatient BPJS Health claim files in February. In testing data analysis using SPSS, based on the results of the simple linear regression test and the significance of α=5% (0.05) or a confidence level of 95% shows that tcount > ttable, meaning that the completeness of the BPJS outpatient claim requirements files influences the quality of claims at the Muhammadiyah Hospital in Bandung. The influence is 69.5% of the completeness variable for outpatient BPJS claims on claim quality, while the remaining 30.5% is influenced by other variables error (e).